DETERMINATION OF TECHNOLOGY OF MANUFACTURE AND MARK OF MINERAL TRANSFORMER OILS BY THEIR OPTICAL SPECTRA - M. Sh. Garifullin; R. A. Giniatullin; V. K. Kozlov; R. L. Rezatdinov; G. I. Rizvanova (Известия высших учебных заведений: Проблемы энергетики)
Conducted analysis of optical transmission spectra mineral transformer oils in the range of 300 - 1000 nm. Showing influence at optical transmission spectrum of transformer oils technologies of their production, as well as used in the production of petroleum raw materials. The algorithm is developed determination of the oil grade according to its transmission spectrum.